2003
DOI: 10.1007/s00299-003-0650-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct somatic embryogenesis and synthetic seed production from Paulownia elongata

Abstract: We have developed a reproducible system for efficient direct somatic embryogenesis from leaf and internodal explants of Paulownia elongata. The somatic embryos obtained were subsequently encapsulated as single embryos to produce synthetic seeds. Several plant growth regulators [6-benzylaminopurine, indole-3-acetic acid, alpha-naphthaleneacetic acid, kinetin and thidiazuron (TDZ)] alone or in combination were tested for their capacity to induce somatic embryogenesis. The highest induction frequencies of somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 36 publications
6
58
0
2
Order By: Relevance
“…Proses perendaman Na-alginat di dalam larutan CaCl 2 dilakukan selama 40 menit. Hal tersebut berfungsi untuk menyempurnakan pembentukan kapsul (Ipekci & Gozukirmizi, 2003). Kapsul yang telah terbentuk kemudian diinkubasi didalam media semi solid pada intensitas cahaya ±88 lux dengan suhu 4 o C.…”
Section: Benih Sintetik Tanaman Tebu Var Nxi 1-3unclassified
“…Proses perendaman Na-alginat di dalam larutan CaCl 2 dilakukan selama 40 menit. Hal tersebut berfungsi untuk menyempurnakan pembentukan kapsul (Ipekci & Gozukirmizi, 2003). Kapsul yang telah terbentuk kemudian diinkubasi didalam media semi solid pada intensitas cahaya ±88 lux dengan suhu 4 o C.…”
Section: Benih Sintetik Tanaman Tebu Var Nxi 1-3unclassified
“…Artificial seeds of Paulownia elongata were produced by the encapsulation of somatic embryos with a conversion rate that was assessed to be 50.3% [51]. A 26% conversion rate was obtained by culture-encapsulated somatic embryos of Quercus robur in P 24 medium supplemented with 0.1 µM IBA, 0.9 µM BA, and 3% sucrose [51]. Kumar et al [53] reported a 47% conversion rate of Oryza sativa cultured in Whatman filter paper.…”
Section: Somatic Embryosmentioning
confidence: 99%
“…artificial seeds produced by the encapsulation of their somatic embryos. Artificial seeds of Paulownia elongata were produced by the encapsulation of somatic embryos with a conversion rate that was assessed to be 50.3% [51]. A 26% conversion rate was obtained by culture-encapsulated somatic embryos of Quercus robur in P 24 medium supplemented with 0.1 µM IBA, 0.9 µM BA, and 3% sucrose [51].…”
Section: Somatic Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted at Fort Valley State University, Fort Valley, GA, U.S.A. indicate that three-year-old trees can reach a diameter of 14.8 cm and achieve a height of 8.31 m (Basu et al 2015). The tree benefits from not requiring replanting and can be used for fodder and medicinal purposes (Ipekci & Gozukirmizi 2003). New shoots sprout from a stump after harvesting and grow as much as 20 feet in the first growing season (Basu et al 2015).…”
Section: Introductionmentioning
confidence: 99%